NOMINAL GROUP IN THE MOVIE SCRIPT OF FINDING NEMO - Adi Sutrisno; Suci Fitrianis Lestari (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
Nominal group is one of the types of groups that have functional components that is wider in the structure in between the other group, as advanced Thompson (2000:181) the nominal group is the grammatical unit that has the most variety at this rank of groups and this bolster consumers consumption allow the widest range of meanings to be expressed describing the types of nominal group pattern produced by movie script and the dominant nominal group. Research design of this thesis is descriptive qualitative method. Meanwhile, the data of this research were taken from movie script in the internet. Analysis method of this reseach is spradly method such as domain,taxonomy and componential, to obtain the degree of validity and reliable data of this research, the researcher used triangulation method and triangulation source. The result shows that there are 10 construction of nominal group. highest nominal group pattern produced is D+T pattern with 25 number, it indicates that the researcher mostly produced definite and indefinitine in this analysis, then it is followed by D+E+T pattern with 9 numbers, after that it is followed by D+C+T with 4 numbers and N+T 3 numbers continued with D+N+T pattern with 2 numbers, for the patterns C+T produced 1 numbers and for the pattern D+T+Q produced 2 number then pattern N+T+Q produced 1 number continued with D+N+E+T pattern produced 1 number, the last number of the nominal group pattern is D+E+T+Q with 2 numbers and it means the researcher produced 44 numbers of Deictic, 50 numbers for Thing, 11 numbers of Epithet, 5 numbers of Classifier, 5 numbers of qualifier and 6 numbers for Numeral.